Description of resilience in patients Cancer at Haji Adam Malik hospital Medan in 2022 - Vina Y.S. Sigalingging; Friska Ginting; Helinida saragih; Luber Nia Halawa (Sean Institute, 2024)
Cancer is defined as the abnormal growth of cells caused by several changes in gene expression that cause dysregulation of cell proliferation and cell death. The type of research design used is descriptive with a purposive sampling method and the instrument used in this research is a resilience questionnaire. Result: 47 respondents (85.5%) were female and 8 respondents (14.5%) were male, Early elderly (46-55) were 28 respondents (50.9%) and late teenagers 17-25 were 2 respondents (3.6%), married status was 49 respondents (89.1%) and unmarried was 1 respondent (1.8%), housewives work as many as 21 respondents (38.2%) and civil servants as many as 2 respondents (3.6%), slam was 25 respondents (45.5%) and Catholicism was 8 respondents (14.5%), the Javanese were 22 respondents (40%) and the Padang tribe was 1 respondent (1.85), diagnosis of mammary cancer was 43 respondents (78.2%) and melanoma was 3 respondents (5.5%), the duration of cancer > 6 months was 42 respondents (76.4%) and 13 respondents (23.6%), 13 respondents (23.6%) had very high resilience and 4 respondents (7.3%) had very low resilience. Conclusion: It is hoped that cancer sufferers will become more aware of their ability to increase resilience, especially for patients who have low resilience.